2022
DOI: 10.1111/pbi.13775
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐level Thlaspi arvense genome provides new tools for translational research and for a newly domesticated cash cover crop of the cooler climates

Abstract: Summary Thlaspi arvense (field pennycress) is being domesticated as a winter annual oilseed crop capable of improving ecosystems and intensifying agricultural productivity without increasing land use. It is a selfing diploid with a short life cycle and is amenable to genetic manipulations, making it an accessible field‐based model species for genetics and epigenetics. The availability of a high‐quality reference genome is vital for understanding pennycress physiology and for clarifying … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 148 publications
(202 reference statements)
5
64
0
Order By: Relevance
“…The species is an interesting study object also because it is currently being domesticated into a new biofuel and cover crop [37][38][39][40][41]. The genomic work with T. arvense is facilitated by recently published high-quality reference genomes [36,42]. In our study, we demonstrate that European populations of T. arvense harbour substantial natural epigenetic variation, which is associated with DNA sequence variation as well as with climate of origin, but in a highly contextdependent manner.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…The species is an interesting study object also because it is currently being domesticated into a new biofuel and cover crop [37][38][39][40][41]. The genomic work with T. arvense is facilitated by recently published high-quality reference genomes [36,42]. In our study, we demonstrate that European populations of T. arvense harbour substantial natural epigenetic variation, which is associated with DNA sequence variation as well as with climate of origin, but in a highly contextdependent manner.…”
Section: Introductionmentioning
confidence: 56%
“…We not only distinguished PLOS GENETICS between the three sequence contexts CG, CHG and CHH, but we also assigned cytosines to different genomic features: CDS, introns, promoters, TEs and intergenic regions. For genes and TEs, we used available annotations [36], while for promoters we considered the 2 kb upstream sequences of genes (or until the boundary of the previous gene if closer). We considered intergenic space, anything not belonging to these categories.…”
Section: Average Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has long been established that DNA methylation is enriched in peri−/centromeric regions which follow the distribution of TEs over the chromosomes of genomes of the Brassicaceae family, as recently also confirmed for Thlaspi arvense [ 67 , 68 ]. In our study, while investigating the global distribution of DMRs over the F. vesca chromosomes, we found that regions with high DMR density correlated with regions enriched in Helitrons .…”
Section: Discussionmentioning
confidence: 91%